Patient characteristics associated with greater blood pressure control in a randomized trial of home blood pressure telemonitoring and pharmacist management - Asche, Stephen E. (J Am Soc Hypertens, 2016)
This paper reports subgroup analysis of a successful cluster-randomized trial to identify attributes of hypertensive patients who benefited more or less from an intervention combining BP telemonitoring and pharmacist management. The endpoint was BP <140/90 mm Hg at six-month follow-up. Fourteen baseline patient characteristics were selected a-priori as subgroup variables. Among the 351 trial participants, 44% were female, 84% non-Hispanic white, mean age was 60.9 years, and mean BP was 149/86 mm Hg. The overall adjusted odds ratio for BP control in the intervention vs. usual care group was 3.64 (p<0.001). The effect of the intervention was significantly larger in patients who were younger (interaction p= 0.02), did not have diabetes (p=0.005), had high baseline DBP (p=0.02), added salt less than daily in food preparation (p=0.007), and took 0–2 (rather than 3–6) antihypertensive medication classes at baseline (p=0.02). These findings may help prioritize patients for whom the intervention is most effective.